An evaluation on the effectiveness of web-based virtual tour interfaces - Abu Bakar, Juliana Aida (Universiti Utara Malaysia, 2006)
Virtual tour is often expected to give prospective clients overview of intended places for future visits such as universities, colleges, campus, and tourist attractions.As far as sports center is concerned, virtual tour is used to attract more users to utilize the facilities provided by making them aware of what facilities are available. However, there is currently lacking of literature to support whether virtual tour is effective in promoting sports and recreational facilities.On the other hand, there are user studies carried out to evaluate the effectiveness of two-dimensional (2D) and three-dimensional (3D) interfaces in various domains.Hence, this study aims to contribute in the list the domain of virtual tour.Three following objectives were outlined: (a) to measure task performance for 2D and 3D virtual tour interfaces, (b) to determine the relationship between virtual tour interfaces and effectiveness of a virtual tour, and (c) to determine the priority (importance) of features to be incorporated in a virtual tour.A quasi-experimental research method was performed using a task sheet and a set of questionnaire to achieve the objectives of this study.The findings of this study contribute empirical evidence that virtual tour is effective in promoting sports and recreational facilities in terms of its functionalities, user level of awareness, and user intention to use.It also contributes to the list of user studies on 2D and 3D interfaces particularly in the domain of virtual tour.Finally, the deliverables of this study may serve as guidelines to future virtual tour development projects.